Descriptive Study of Tracer Study On The Profile Of UHAMKA Master of Basic Education Graduates - Amaliyah, Nurrohmatul; Kosasih, Kosasih; El Vitra, Rina; Pebriansyah, Aditya (Devotion : Journal of Research and Community Service, 2023)
This tracer study tracking graduates aims to identify the profile of master's degree graduates in basic education which includes: (1) student study period, (2) graduate waiting period, (3) work motivation, (4) job suitability with the field of science, (5) income received, and (6) the expectations of the institution/place of work for the knowledge that has been obtained during the master's level of basic education at UHAMKA. This type of research is a type of survey research with a descriptive evaluative research approach. The subjects of this research are alumni of the Master of Basic Education study program at UHAMKA with a total of 110 students and alumni users, both government and private. The data collection technique used in this study was a questionnaire, both open and closed. The data analysis technique used in this research is descriptive data analysis. Descriptive analysis in this study was carried out by using the frequency distribution tabulation technique and histogram, and equipped with a narrative explanation.